New materials and technologies for healthcare - Hench, Larry L., 1938-; Jones, Julian R.; Fenn, Michael B. (Imperial College Press, 2012)
"This volume summarizes recent developments in the use of new materials and technologies in healthcare. The emphasis is on new approaches that incorporate bioactive materials and scaffolds with cells in the emerging technologies of tissue engineering and regenerative medicine. The incorporation of nanotechnology, stem cells, and gene control of cells is included in the current research discussed" ---Zadní s. obálky
Keywords: biologické materiály; biomedicína; nanomedicína; regenerační medicína; biologicky aktivní látky; tkáňové inženýrství; biomedicínské inženýrství; biological materials; biomedicine; nanomedicine; regenerative medicine; bioactive compounds; tissue engineering; biomedical engineering; kolektivní monografie; elektronické knihy; collective monographs; electronic books